PELAKSANAAN PERATURAN DAERAH PROVINSI BALI NOMOR 10 TAHUN 2011 TENTANG KAWASAN TANPA ROKOK DALAM RANGKA PERLINDUNGAN TERHADAP PEROKOK PASIF - I Komang Wijana; I Nyoman Mudana (Kertha Negara : Journal Ilmu Hukum, 2014)
This research, entitled "Implementation of the Regulation of Bali Province No. 10 Year2011 about No Smoking Area Protection in the Context of Passive Smokers". Thebackground of the problems in this research that there are many smokers who smokefreely in any place in terms of not only detrimental to the health of smokers themselve ,but also harms the people around him as a result of exposure to cigarette smoke.Normatively since 2001 Government of Bali Province has rules about No Smoking Areathrough the Regulation of Bali Province No. 10 Year 2011. Based on this background,the problems in this research include: the authority of the Government of Bali Provincein No Smoking Area arrangements and the implementation of the Regulation of BaliProvince No. 10 Year 2011 about No Smoking Area in order to protect againstsecondhand smoke. This research is an empirical legal research, which emphasizes theeffectiveness of the law, which is based on sources of primary legal materials andsecondary legal materials. Based on the discussion of this research, its obtainedresearch results that the Government of Bali Province authorities for the organizationof Smoking Area, but has not been effective, because they found smokers who smokecigarettes even though the region has been performed with prosecution.